Improving Critical Thinking Skills of Early Childhood through Inquiry Learning - Nita Priyanti; Jhoni Warmansyah (LPPM Universitas Pahlawan Tuanku Tambusai, 2021)
21st-century skills that children must have, namely the ability to collaborate, create, communicate and think critically. This study aims to improve critical thinking skills in children to adapt to their time. This research was conducted in group B of the Kindergarten in Madinah Pamulang, South Tangerang with a total of 20 children. The research method uses classroom action research with 2 cycles. Collecting data by means of observation, interviews, documentation and the data obtained were analyzed using quantitative and qualitative. The results showed that the children's critical thinking skills increased by 18.4% in cycle I and cycle 2 by 45% after research and corrective action were carried out. The results of the action in the second cycle of 45% prove that the children's critical thinking skills have increased significantly. Improvement occurs through simple experimental activities with the stages of problem finding, exploration, creation, and reflection. The conclusion of this study is that critical thinking skills in early childhood can be improved through inquiry learning.